PERTUMBUHAN JANGKRIK PADA PEMELIHARAA INTENSIF DENGAN PADAT PENEBARAN DAN JENIS PAKAN YANG BERBEDA - Ihlas AG, Muhammad; Saili, Takdir; Nafiu, La Ode (Indonesian Journal Of Animal Agricultural Science (IJAAS), 2019)
The growth of such animal included cricket is more dependent on quantity of food on cricketgrowth was evaluated using factorial-based randomized completed design with 3 replications. The first factor was stocking density with 3 levels, 80 crickets/box (P1), 160 crickets/box (P2), and 240crickets/box (P3). While second factor was tyepe of feeds with 3 levels, mustard leaves (R1), papaya(R2), and sweet potato leaves (R3). The Research Was Conducted in Poultry Breeding Unit of AnimalScince Faculty, University Halu Oleo from May to July 2015. Parameters measured were feed intake,weight gain, feed conversion and mortality. The results showed that there were no interaction effect ofstocking density and feed type on all parameters measured, except for mortality. The same effect was alsoshowed by the solo effect of stocking density. However, the solo effect of feed type showed significanteffect on feed intake, weight gain and feed conversion. Finally, in was concluded that crickets feed bymustard leaves on different stocking density achieved highest weight gain and lowest mortality than feedby papaya and sweet potato leaves. However, feed conversion papaya fruit was lower (P<0.05) incomparison with other types of feed, making it more efficient. Keywords: cricket, stocking density, feed types, weight gain, mortality